The French and Indian Wars the story of battles and forts in the wilderness - Hamilton, Edward P. (Mainstream of America series, 1962)
The author reconstructs the picture of the ragged men, the battles and sieges during this long series of wars which began in the 1690's. He show how the French colonies spanned the continent while the English lay on the seacoast, and points out that the basic conflict occurred as the English desperately tried to penetrate the barrier of the Appalachians. He also discusses the controversial role of the Indian in these wars. (Publisher)